Comparative study of methods for solving the Rubik’s Cube / Nur Syahirah Shuhaimi & Noor Fazlini Mustari - Shuhaimi, Nur Syahirah; Mustari, Noor Fazlini (2019)
Solving Rubik’s cube can be using software or layer-by-layer human method. This study are to analyze and compare between two different methods for solving Rubik’s cube. Therefore, many researches incline to use layer-by-layer human for solving the Rubik’s cube. Through this project, the study method of layer-by-layer human which are Fridrich and ZZ method are being applied. Moreover, this project is focusing more on Fridrich method in finding the best time taken for solving the Rubik’s cube rather than ZZ method. The factors that were considered are the minimum, maximum and average of the moves and times of Fridrich Method (CFOP) requires for solving Rubik’s Cube, how many moves and times to solve per algorithm. The mathematics behind the steps for solving Rubik’s cube are observed. Besides, from the observation, there are commutative, conjugate, association and inverse through random jumble of Rubik’s cube. Since the efficiency were factored by move and time of each method by several algorithms, the movement of each method of several algorithms will be determined the efficiency for solving the Rubik’s Cube. The conclusion, the data of moves and times by Fridrich Method (CFOP) were collected from beginner. For each several algorithms that are going to compare between Fridrich Method (CFOP) and ZZ Method will determine the best method for solving the Rubik’s Cube. From the result, the ZZ method is the most efficiency and the best method for solving the Rubik’s cube which is, 102.30s compared to Fridrich method which is, 146.20s.